KEILAHIAN YESUS DALAM INJIL YOHANES 6:16-21 MENURUT PERSPEKTIF GENRE FANTASTIS TZVETAN TODOROV - Maichelian Siahaan; Hanry Caesar Chandra (Sekolah Tinggi Teologi Ekumene Jakarta., 2021)
The Gospel of John presented many miracle stories of Jesus that contain particular theological ideas. One that particular story was the story of Jesus walking on the sea in John 6:16-21. This particular story was great to research because it had fantastic narrative aspects. For that reason, this research used fantastic literature hermeneutic approach by Tzvetan Todorov to find the meaning of the text behind the miracle story in John 6:16-21. According to the analysis, two perspectives of the fantastic genre operated in it. First, in the character’s perspective and the second one in the reader’s perspective. From both perspectives, ambiguity can be seen within the characters in the story and also the reader which tried to understand the story. On the other hand, the concept of Jesus’s divinity which is seen in the fantasy genre can also create faith escalation to the readers or believers.